CLICO Sforzata Takes Prestigious Title for the First Time - Cardinez, Gary (Daily Express)
CLICO Sforzata takes the prestigious "Pan in the 21st Century" title for the first time. Sforzata performed Dr. Jeannine Remy's arrangement of Jasmine Sullivan's, "I Bust the Windows of Your Car".
Keywords: Steel band music -- Competitions -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago; Steel bands (Music) -- Competitions -- Trinidad and Tobago